Pengembangan Qalb Melalui Pendekatan Multiple Intelligence - Afrinaldi, Afrinaldi (TAJDID, 2016)
This paper is aimed at finding out the development of the potency of the mind through double intelligence approach (intellectual intelligence, emotional intelligence and spiritual intelligence). All intelligence potencies that human posses will end on the culmination point known as the spiritual satisfaction with the ability to find God through the spiritual intelligence. Many people become successful with the help of their intellectual intelligence, but they failed to communicate, or they have intellectual and emotional intelligence but they lack of spiritual intelligence and finally they are dragged into the valley of sins and failure. This paper tries to offer a new vision on how to integrate the three intelligence potency which can be actualized through certain values; honesty, courtesy and tenderness. One of the most possible methods is by analyzing the potency of the mind as a standard in performing any kinds of activities (individual and social deeds) to possess spirituality. This paper is design as an alternative idea to develop the mind which are considered pure and that the value of the God-Fearing can be manifested in daily lives.